2018
DOI: 10.1016/j.echo.2018.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Load Dependency of Left Atrial Strain in Normal Subjects

Abstract: In normal subjects, LA strain is preload dependent but to a lesser degree than LA volume. This difference underscores the relative advantage of LA strain over maximum volume, when LA assessment is used as part of the diagnostic paradigm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 35 publications
2
36
0
5
Order By: Relevance
“…The reduction in LA contractile function in patients with AR might be explained by an increased afterload imposed on the left atrium caused by a combination of competitive filling of the left ventricle from the aorta and increased stiffness of the LV wall. LA phasic function is also directly influenced by preload, as demonstrated in a study of healthy volunteers, where all LAS components were reduced following an acute preload reduction [39]. The reduction in volume load and LV preload following aortic valve surgery improved LAS components in our patients with AR.…”
Section: Systolic LV Functionsupporting
confidence: 68%
“…The reduction in LA contractile function in patients with AR might be explained by an increased afterload imposed on the left atrium caused by a combination of competitive filling of the left ventricle from the aorta and increased stiffness of the LV wall. LA phasic function is also directly influenced by preload, as demonstrated in a study of healthy volunteers, where all LAS components were reduced following an acute preload reduction [39]. The reduction in volume load and LV preload following aortic valve surgery improved LAS components in our patients with AR.…”
Section: Systolic LV Functionsupporting
confidence: 68%
“…The poor test-test reproducibility of LA strain could also be related to the change LA filling states between the two scans. However, it has been shown that strain is less affected by preload than the volume assessment [ 39 ] and our date shows volumetric assessment to have better test-test reproducibility than strain.…”
Section: Discussionmentioning
confidence: 78%
“…It is known that 3DSTE suffers from inherently lower image quality than 2D echocardiography due to the low temporal and spatial image resolutions (low rate of volume acquisition, insufficient number of crystals, etc. ); therefore, further technical improvements are warranted. LA appendage and pulmonary veins were excluded from measurements, which could theoretically affect the results. LA strains are important LA functional features 19 . Although parallel LA strain measurements could be performed together with volumetric assessments at the same time from the same 3D echocardiographic datasets, they were not presented.…”
Section: Discussionmentioning
confidence: 99%
“…4 LA strains are important LA functional features. 19 Although parallel LA strain measurements could be performed together with volumetric assessments at the same time from the same 3D F I G U R E 4 Gender-dependency of left atrial emptying fractions over age decades as assessed by three-dimensional speckle-tracking echocardiography. Lines represents significant differences between the groups.…”
Section: Limitation Sectionmentioning
confidence: 99%